STUDI TENTANG KEMAMPUAN MAHASISWA SEMESTER EMPAT FKIP BAHASA INGGRIS UNIVERSITAS RIAU DALAM MENULIS RINGKASAN FILM PENDEK - Annisa Gebrina; Syofia Delfi; Desri Maria Sumbayak (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study presents the ability of fourth semester students of English Study Program University of Riau in writing summary of a short movie .This study was based on fourth semester students’ experiences that have learned writing summary text in second semester. Moreover, fourth semester students’ also have learned about literature in third semester in Introduction to Literature subject. Because the fourth semester students will learn literature subjects in next semester, they should be able to write summary in another source, for example from movie. The participants were 38 students of fourth semester students English Study Program University of Riau. The participants were selected randomly from two classes. This study was conducted in one writing test based on Harris (1986) criteria. The instruments of the research were one writing form and short movie entitled Now or Never (Youtube.com). The research finding showed there were fewer students got satisfied score, which was the average of fourth semester students’ ability in writing summary of a movie fall into poor to average level. Based on this finding, it was suggested to fourth semester students of English Study Program University of Riau to develop their skill in grammar, mechanic, fluency and organization because these were the important aspects in learning a language especially in writing.Keywords: writing summary, using short movie, fourth semester students’ ability.